1969
DOI: 10.1029/jb074i022p05221
|View full text |Cite
|
Sign up to set email alerts
|

Geological-geophysical interpretation of Mono Basin, California-Nevada

Abstract: The geology of the margins of the Mono basin, California, suggests that the basin is a relatively shallow warp. When interpreted in the light of detailed study of the basin fill and of the geologic history of the region, the gravity and seismic data are consistent with the basin's being filled to a depth of 1 to 1.5 km, largely with sedimentary deposits. The geophysical data have been interpreted by others to indicate that the basin subsided deeply along nearly vertical faults and is filled to a depth of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Early gravity investigations suggested that the magmatic source was under the west side of Mono Craters, which was interpreted as a collapsed caldera [ Pakiser et al , ], but no such structure was found from seismic data [ Gilbert et al , ; Christensen et al , ; Hill et al , ] nor MT data [ Hermance et al , ]. Hermance et al [] did not find a low resistivity anomaly below Mono Craters and suggested that if there is one, it has to be at least 8 km deep.…”
Section: Previous Geophysical Work In Mono Basinmentioning
confidence: 99%
“…Early gravity investigations suggested that the magmatic source was under the west side of Mono Craters, which was interpreted as a collapsed caldera [ Pakiser et al , ], but no such structure was found from seismic data [ Gilbert et al , ; Christensen et al , ; Hill et al , ] nor MT data [ Hermance et al , ]. Hermance et al [] did not find a low resistivity anomaly below Mono Craters and suggested that if there is one, it has to be at least 8 km deep.…”
Section: Previous Geophysical Work In Mono Basinmentioning
confidence: 99%
“…Model l 's basement is shallower than that proposed by Pakiser (1970), but Model 2's basement is locally deeper than that analyzed by Christensen et al (1969). Because the calculated gravity anomaly is strongly influenced by the low-density lacustrine sediments, the proposed gravity inversion process with more detailed information about this sediment's density variation may provide a better understanding of the tectonic setting of the basin.…”
Section: Real Casementioning
confidence: 79%
“…Pakiser et al (1960) and Pakiser (1968Pakiser ( , 1970) (Model 1) assumed that the basin is a deeply downfaulted structural block. Christensen et al (1969) (Model 2) considered a broad, shallow downwarp. In both cases, the associated gravity anomaly was modeled by forward computations based on a variety of possible density distributions.…”
Section: Real Casementioning
confidence: 99%
“…Here we argue that the region between the Excelsior Mountains and White Mountains served, and continues to serve, as a “zone of weakness” to funnel deformation across the Mono Basin into the central Mina Deflection due to crustal anisotropy (Figure ). Recent and historic magnetic and gravity data in the area between Excelsior Mountain and the White Mountain structural blocks show gradients in both total field magnetic and isostatic residual gravity data (Bursik et al, ; Christensen et al, ; Gilbert et al, ; McDonell, ; Pakiser et al, ; Roberts & Jachens, ). A pronounced magnetic high occurs just west of the Adobe Hills (Adobe Flats) at the California‐Nevada border that increases rapidly into the western Mina Deflection just south of Huntoon Valley (Appendix Ca).…”
Section: Discussionmentioning
confidence: 99%